West nile virus isolation in human and mosquitoes, Mexico - Elizondo Quiroga, Darwin; Davis, Todd C.; Fernández Salas, Ildefonso; Escobar López, Román; Velasco, Dolores; Soto, Lourdes Cecilia; Aviles, Magaly; Elizondo Quiroga, Armando Erick; González Rojas, José Ignacio; Contreras Cordero, Juan Francisco; Guzman, Hilda; Travassos Da Rosa, Amelia; et al. (National Center for Infectious Diseases, Centers for Disease Control and Prevention (CDC), 2005)
West Nile virus has been isolated for the first time in Mexico, from a sick person and from mosquitoes (Culex quinquefasciatus). Partial sequencing and analysis of the 2 isolates indicate that they are genetically similar to other recent isolates from northern Mexico and the western United States. Several recent reports have documented the widespread geographic distribution of West Nile virus (WNV) in Mexico, but until now, no autochthonous human cases of illness due to this virus have been reported from the republic. Likewise, limited entomologic surveillance has been conducted in Mexico, and no information is available on the actual mosquito vectors of WNV in the republic. All Mexican WNV isolates studied to date have come from dead equines or birds. We report the first isolations of WNV from a sick person and from a pool of Culex quinquefasciatus mosquitoes and describe their phylogenetic relationship to other representative WNV strains from the United States and Mexico.